UPAYA MENINGKATKAN KEMAMPUAN MENULIS TEKS BIOGRAFI SISWA KELAS X SMA NEGERI 7 PALEMBANG MELALUI MODEL PEMBELAJARAN THINK TALK WRITE - Kiki Rezeki Amelia; Pischa Putri Meiranda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research is motivated by the problem of the lack of ability of students in class X SMA Negeri 7 Palembang in the learning material of writing biography text. The purpose of this research is to improve students' ability in writing biography text. The method used was experiment method. From the research findings that have been carried out in cycle I learning and cycle II learning, it indicates an increase in student learning outcomes in Indonesian language subjects on biography text material with the resulting value in cycle I pretest average 59.34, maximum value 75, minimum value 50, and completeness rate 26.3%. As well as the value generated in Cycle I post test with an average value of 72.89, a maximum value of 85, a minimum value of 60, and a completeness rate of 76.3%. In Cycle II learning, the average value obtained in the pretest was 77.9, the maximum value was 91, the minimum value was 60 and the completeness rate was 84.2% while the average value of the post test was 85.3, the maximum value was 98, the minimum value was 60 and the completeness rate was 89.4%. The use of the Think Talk Write learning model can overcome those in the problem formulation, such as the low learning outcomes of students in Indonesian language subjects. All of that can be seen from the increase in the learning success of class X students from cycle I to cycle II in learning to write biography text.